THE INTENSITY OF THE APPLICATION OF INFORMAL ECONOMIC EDUCATION, SOCIOECONOMIC STATUS OF PARENTS AND POCKET MONEY ON THE RATIONALITY OF SPENDING SOCIAL STUDIES STUDENTS CLASS XI SMAN 2 MALANG - nabilah, ayu; Wahyono, Hari (Sekolah tinggi ilmu ekonomi pemuda, 2023)
In today's modern era, many students like to follow trends and sometimes they act consumptively (irrationally) when shopping. Lack of basic understanding of economic education by parents and management of pocket money given by parents to children. Therefore, a study was conducted on the intensity of the application of informal economic education, socioeconomic status of parents, and pocket money on the rationality of social studies class XI students at SMAN 2 Malang. This study aimed to analyze the intensity of the application of informal economic education, socioeconomic status of parents, and pocket money on the rationality of social studies class XI students of SMAN 2 Malang. This research uses a quantitative approach with explanatory methods. This research was conducted at SMAN 2 Malang Class XI IPS with a population of 163 students from class XI IPS 1,2,3 and 4, while the sample in this study was 96 students calculated using the Daniel &; Terrel formula with proportional sampling. technique. The data analysis used is Multiple Linear Regression Analysis with the help of SPSS 22. The results of the analysis in this study show that: 1) the intensity of the application of informal economic education affects the rationality of spending, 2) the socioeconomic status of parents influences the rationality of spending, 3) pocket money affects the rationality of spending, 4) the intensity of implementing informal economic education, status parents' social economy and pocket money have a significant effect on the rationality of expenditures of class XI IPS students of SMAN 2 Malang .